Prevalencia De Anemia Y Su Relación Con La Fracción De Eyección Y La Clase Funcional En Pacientes Adultos Con Insuficiencia Cardiaca Crónica. - Velarde Díaz, Carlos Alberto (2014)
Background: Heart failure (HF) is considered as a public health problem in rapid growth and its relation to anemia is a fact that has made a recent major, but little considered in clinical practice. Studies that measured the prevalence of anemia in patients with HF have widely varying results so the magnitude of the problem is unclear. Some studies have examined the relationship between anemia and the severity of HF, hospitalization days and mortality and have shown that there is a significant relationship between these variables and anemia. Objective: To determine the prevalence of anemia and its relation to functional class and ejection fraction in adult patients with Chronic Heart Failure in San Pablo Clinic during the period 2002-2013. Method: 176 patient records had been chosen randomly from patients diagnosed with IC in San Pablo Clinic during the period 2002-2013. Data on age, gender, hemoglobin level, ejection fraction and NYHA functional class (New York Heart Association) had been collected. The prevalence of anemia and mean hemoglobin was found and the relationship with ejection fraction and NYHA functional class was determined. Results: Of the sample of 176 medical records found that 102 patients (57.95%) were male and 74 patients (42.05%) were women, with an average age of 75.37 years and a hemoglobin level of 11.98 g / dl. By chi - square test was determined that there is a highly significant relationship between the prevalence of anemia and ejection fraction and NYHA functional class (p < 0.001). It was also observed that the mean hemoglobin was gradually falling from 13.48 g / dl in NYHA I functional class to 10.63 g / dl in NYHA IV functional class (p < 0.001 ) and from 12.33 g / dl in the group with normal EF up to 10.81 g / dl in the group with reduced EF (p < 0.05) Conclusion: If there is a relationship between the prevalence of anemia and ejection fraction and functional class. Hemoglobin levels are lower in the more severe is the IC and systolic function is affected.